Rubberized geopolymer composites: A comprehensive review. Issue 17 (1st September 2022) - Qaidi, Shaker M.A.; Mohammed, Ahmed S.; Ahmed, Hemn Unis; Faraj, Rabar H.; Emad, Wael; Tayeh, Bassam A.; Althoey, Fadi; Zaid, Osama; Sor, Nadhim Hamah
Abstract: The construction sector has been addressing the issue of integrating sustainability into production processes over the last few years, either through solid waste materials as aggregates in concrete or the search for more eco-friendly raw materials. Besides, the global trends group focused on developing an alternative to cement, which is a significant contributor to pollution of the environment due to its greenhouse gas emissions. Geopolymer (GP) is one of the most acceptable solutions for utilizing all industrial by-products containing an alumino-silicate (A-S) source material. However, one method to recycle waste rubber tires is incorporating them into geopolymer concrete (GPC) as an alternative to natural aggregates. Recently, the potential of combining the advantages of GPC with rubberized concrete to produce rubberized geopolymer concrete (Ru-GPC) as a viable, sustainable building material has been recognized. This paper presents a state-of-the-art review of the waste rubber's environmental and economic impact, resources, recycling, classifications, and physicochemical properties. Besides, this article provides in-depth studies on the behaviors and properties of Ru-GPC composites, such as their basic components, preparation and curing processes, fresh and physical properties, mechanical properties, dynamic properties, durability properties, microstructures, and insulation properties. The effect of crumb rubber (CRu) substitution on critical properties is addressed critically. Also, it highlights the applications, embodied CO2 emissions, and cost analysis of Ru-GPC. Moreover, gaps in the literature and recommendations for future study have been identified to support further developments in the investigation and future publication of Ru-GPC materials in practice.